Method for Preparing Pnictogen Polyanion Copolymer Precursor, Method for Preparing Pnictogen-based Semiconductor Nanocrystal Using Same and Optoelectronic Device Comprising Pnictogen-based Semiconductor Nanocrystal

KR103021521B1Active Publication Date: 2026-09-18INDUSTRY UNIVERSITY COOPERATION FOUNDATION HANYANG UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020240067869
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-05-24
Publication Date
2026-09-18
Estimated Expiration
2044-05-24

Smart Images

  • Figure 112024056524350-PAT00001_ABST
    Figure 112024056524350-PAT00001_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing a nictogen polyanionic copolymer precursor, a method for manufacturing a nictogen-based semiconductor nanocrystal using the same, and an optoelectronic device comprising a nictogen-based semiconductor nanocrystal. In the present invention, a novel nictogen polyanionic copolymer precursor is prepared by combining a nictogen element (Group V element) precursor and an organic ligand material to form a complex, and then mixing in a reducing agent. The nictogen polyanionic copolymer precursor according to the present invention has stable reactivity and is easy to handle. Using this, it is possible to synthesize nictogen-based quantum dots with a particle size of 5 nm or more capable of responding in the SWIR region, and nanocrystals can be prepared using various solution synthesis methods.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a method for preparing a nictogen polyanionic copolymer precursor, a method for preparing a nictogen-based semiconductor nanocrystal using the same, and an optoelectronic device including a nictogen-based semiconductor nanocrystal. More specifically, the invention relates to a method for preparing a nictogen polyanionic copolymer precursor by reducing a complex of a nictogen element precursor and an organic ligand, a method for preparing a nictogen-based nanocrystal using the same, and an optoelectronic device including a nictogen-based semiconductor nanocrystal. Background Technology

[0002] As the Fourth Industrial Revolution develops, the market for next-generation display devices, imaging sensors, and infrared sensors such as LiDAR sensors is growing, and the importance of materials used in these devices is emerging. For example, colloidal nanocrystals are used in the active layers of displays and sensors, but conventional nanocrystals containing lead, cadmium, etc., have limitations in use due to environmental regulations.

[0003] Under these circumstances, technology using nictogen (group V)-based semiconductor compounds is being developed. For example, Korean Published Patent Application No. 10-2007-0064554 describes a method for producing nanoparticles such as Zn3As2 by converting precursors containing ions into nanoparticles, and Korean Registered Patent Application No. 10-1593425 describes a method for producing zinc arsenide quantum dots by mixing a zinc precursor and a surfactant, heating the mixture, injecting tritrimethylsilylarsenide as an arsenic precursor into the mixture, and growing crystals.

[0004] The above-mentioned nictogen-based nanocrystals are semiconductor materials with photosensitive properties and can be used in various fields, such as optoelectronic devices. However, nictogen-based semiconductor materials are difficult to synthesize due to strong covalent bonds, requiring very high reactivity in the precursor. As a result, the nictogen precursor has low stability, and there were problems such as oxidation occurring on the surface or reduced crystal uniformity during nanocrystal synthesis. In addition, due to low stability, there was a limitation in that it was difficult to grow the nanocrystals to a size (5 nm or larger) capable of infrared sensitivity during manufacturing.

[0005] Accordingly, there is a need for the development of technology that can improve the stability and ease of handling of nictogen (Group V) precursors. The problem to be solved

[0006] The objective of the present invention is to provide a method for manufacturing a nictogen-based precursor with excellent stability.

[0007] Another objective of the present invention is to provide a method for stably producing nictogen-based nanocrystals using the above precursor.

[0008] Another objective of the present invention is to provide an optoelectronic device manufactured using the nanocrystal. means of solving the problem

[0009] To achieve the above objective, the present invention provides a method for preparing a nictogen polyanionic copolymer precursor, comprising the steps of: mixing a halide of a nictogen (Group V) element and an organic ligand having one or more double bonds within the molecule; and adding a reducing agent to the mixture and further reacting it with the organic ligand to produce a nictogen polyanionic copolymer.

[0010] In the present invention, the halides of the nictogen elements may be one or more selected from the group consisting of arsenic trichloride (AsCl3), arsenic tribromide (AsBr3), arsenic triiodide (AsI3), antimony trichloride (SbCl3), antimony tribromide (SbBr3), antimony triiodide (SbI3), phosphorus trichloride (PCl3), phosphorus tribromide (PBr3), and phosphorus triiodide (PI3).

[0011] In the present invention, the organic ligand may include one or more selected from the group consisting of oleylamine, oleic acid, palmitoleic acid, linoleic acid, linoleylamine, and enamine.

[0012] In the present invention, the mixture can be prepared by reacting the halide of the nictogen element and an organic ligand at 40 to 100°C for 4 to 24 hours.

[0013] In the present invention, the reducing agent may include one or more selected from the group consisting of lithium triethylborohydride (superhydride), diisobutylaluminium hydride (DIBAL-H), lithium aluminum hydride (LiAlH4), lithium borohydride (LiBH4), sodium borohydride (NaBH4), alane N,N-dimethylethylamine complex (DMEA-AlH3), and tris(dimethylamino)phosphine.

[0014] In the present invention, in the step of adding the reducing agent, a step of additionally adding the organic ligand may be further performed.

[0015] In the present invention, the step of adding an organic solvent before adding a reducing agent to the complex may be further performed.

[0016] In the present invention, the organic solvent may include one or more selected from the group consisting of trioctylphosphine (TOP), tributylphosphine, 1-octadecene, 1-undecene, octylamine, oleylamine, hexadecylamine, and trioctylamine.

[0018] The present invention also provides a method for manufacturing a nictogen-based semiconductor nanocrystal, comprising the step of reacting the nictogen polyanionic copolymer precursor and a Group II or Group III precursor to produce a nanocrystal.

[0019] In the present invention, the nanocrystal manufacturing step may include: a step of preparing a mixture by adding a nictogen polyanionic copolymer precursor to a Group II or Group III precursor; a step of increasing the temperature of the mixture at a rate of 0.5 to 10℃ / min to reach a synthesis temperature of 200 to 340℃; and a step of growing crystals at the synthesis temperature for 5 minutes to 12 hours.

[0020] In the present invention, the nanocrystal manufacturing step may include the step of adding a core material to a Group II or Group III precursor and then heating it to 200 to 340°C; and the step of growing crystals at 200 to 340°C for 5 minutes to 12 hours while continuously injecting a nictogen polyanionic copolymer precursor into the heated precursor.

[0021] In the present invention, the nanocrystal manufacturing step may include: heating a Group II or Group III precursor to 200 to 340°C; injecting a nictogen polyanionic copolymer precursor into the heated precursor within 10 seconds; and growing crystals at 200 to 340°C for 5 minutes to 12 hours after the precursor injection.

[0022] In the present invention, it is preferable that the average particle size of the manufactured nanocrystals is 5 to 50 nm.

[0024] The present invention also provides an optoelectronic device comprising an active layer formed using the nictogen-based semiconductor nanocrystal.

[0025] In the present invention, the optoelectronic device can be sensitive to light in the short wavelength infrared (SWIR) region. Effects of the invention

[0026] In the present invention, a novel nictogen polyanionic copolymer precursor is prepared by combining a nictogen element (Group V element) precursor and an organic ligand material to form a complex, and then mixing in a reducing agent. The nictogen polyanionic copolymer precursor according to the present invention has stable reactivity and is easy to handle. Using this, it is possible to synthesize nictogen-based quantum dots with a particle size of 5 nm or more capable of responding in the SWIR region, and nanocrystals can be prepared using various solution synthesis methods. Brief explanation of the drawing

[0027] Figure 1 shows the synthesis mechanism of a nictogen polyanionic copolymer precursor according to one embodiment of the present invention. FIG. 2 schematically illustrates the manufacturing process of a nictogen polyanionic copolymer precursor according to one embodiment of the present invention. Figure 3 shows a photograph of a nictogen polyanionic copolymer precursor prepared according to one embodiment of the present invention. FIG. 4 schematically illustrates the manufacturing process of a nictogen polyanionic copolymer precursor according to another embodiment of the present invention. Figure 5 shows a photograph of a nictogen polyanionic copolymer precursor prepared according to another embodiment of the present invention. Figure 6 shows a photograph of a nictogen complex prepared according to a comparative example of the present invention. Figures 7a and 7b show the MALDI-TOF mass spectrometry results of a nictogen polyanionic copolymer precursor (a) and a precursor (b) after purification, respectively, prepared according to one embodiment of the present invention. Figure 8 shows the nuclear magnetic resonance (NMR) analysis results of a nictogen polyanionic copolymer precursor and an organic ligand according to one embodiment of the present invention. Figure 9 shows photographs of precursor samples by solvent of a nictogen polyanionic copolymer precursor prepared according to one embodiment of the present invention. Figure 10 shows the results of MALDI-TOF mass spectrometry in different solvents of a nictogen polyanionic copolymer precursor prepared according to one embodiment of the present invention. Figure 11 shows the absorption spectrum and TEM image of InAs nanocrystals prepared using a heating method according to one embodiment of the present invention. Figure 12 shows the absorption spectrum and TEM image of InAs shell nanocrystals prepared using a continuous injection method according to one embodiment of the present invention. Figure 13 shows the absorption spectrum and TEM image of InAs nanocrystals prepared using a high-temperature injection method according to one embodiment of the present invention. Figure 14 shows the absorption spectrum and TEM image of InSb nanocrystals prepared using a high-temperature injection method according to one embodiment of the present invention. Figures 15a and 15b each show the absorption spectra of InAs nanocrystals prepared according to one embodiment of the present invention, according to the type of precursor. Figures 16a and 16b each show TEM images of InAs nanocrystals prepared according to one embodiment of the present invention, categorized by precursor type. Figures 17a and 17b each show the particle size distribution of InAs nanocrystals prepared according to one embodiment of the present invention. Figure 18 shows sample photographs of a nictogen polyanionic copolymer precursor prepared according to one embodiment of the present invention, categorized by solvent. FIGS. 19a, 19b, and 19c each show the absorption spectra of InAs nanocrystals prepared from precursors prepared using TOP(a), ODE(b), and TBP(c) as solvents according to one embodiment of the present invention. FIGS. 20a and 20b each show the absorption spectra of InAs nanocrystals prepared using a nictogen polyanionic copolymer precursor (a) and an As precursor (b) according to one embodiment of the present invention. Figure 21 shows the IV analysis results in the 970 nm and 1,050 nm regions for an optoelectronic device fabricated using InAs nanocrystals according to one embodiment of the present invention. Figure 22 shows the IV analysis results for each precursor of an optoelectronic device fabricated using InAs nanocrystals according to one embodiment of the present invention. Specific details for implementing the invention

[0028] Specific embodiments of the present invention will be described in more detail below. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by a skilled expert in the art to which the present invention pertains. In general, the nomenclature used herein is well known and commonly used in the art.

[0030] The present invention relates to a novel nictogen (Group V) polyanionic copolymer precursor and a semiconductor nanocrystal produced using the same.

[0031] Group V precursors used in the synthesis of Group V compound-based nanocrystals generally possess high reactivity, posing a risk of explosion and prone to oxidation. Furthermore, they have the disadvantage of being difficult to handle due to their toxicity. Consequently, when synthesizing nanocrystals using conventional Group V precursors, size control is difficult; this has resulted in a limitation where it is challenging to synthesize Group V compound-based infrared-sensitive nanocrystals of a size capable of responding to the Short Wavelength InfraRed (SWIR) region.

[0032] The present invention aims to solve the problems of the prior art. In the present invention, a novel nictogen polyanionic copolymer precursor is prepared by combining a nictogen element (Group V element) precursor and an organic ligand material to form a complex, and then mixing in a reducing agent. The nictogen polyanionic copolymer precursor according to the present invention has stable reactivity and is easy to handle. Using this, it is possible to synthesize nictogen-based quantum dots with a particle size of 5 nm or more capable of responding in the SWIR region, and nanocrystals can be prepared using various solution synthesis methods.

[0033] The precursor according to the present invention is a precursor having the form of a nictogen polyanionic copolymer, and the nictogen polyanionic copolymer precursor of the present invention can be synthesized through the steps of: mixing a halide of a nictogen element and an organic ligand; and adding a reducing agent to the mixture and further reacting it with the organic ligand to produce a nictogen polyanionic copolymer.

[0034] In the present invention, a nictogen polyanion refers to a state in which a plurality of nictogen anions are entangled, and according to the present invention, a precursor material can be synthesized in which nictogens in such a polyanion state form a copolymer through an organic ligand. Accordingly, in describing the present invention, the novel precursor material of the present invention is referred to as a "nictogen polyanion copolymer precursor."

[0035] In the present invention, the nictogen element refers to a Group V (Group 15) element and may be one or more of arsenic (As), antimony (Sb), phosphorus (P), and bismuth (Bi). The halides of the Group V elements may include chlorides, bromides, iodides, fluorides, or combinations thereof of the Group V elements. For example, the halides of the Group V elements may include one or more of arsenic trichloride (AsCl3), arsenic tribromide (AsBr3), arsenic triiodide (AsI3), antimony trichloride (SbCl3), antimony tribromide (SbBr3), antimony triiodide (SbI3), phosphorus trichloride (PCI3), phosphorus tribromide (PBr3), and phosphorus triiodide (PI3).

[0036] In the above complex manufacturing step, an organic ligand is mixed with the halide of the nictogen element.

[0037] In the present invention, the organic ligand is a ligand material comprising one or more double bonds within a molecule, and may include one or more selected from the group consisting of oleylamine, oleic acid, palmitoleic acid, linoleic acid, linoleylamine, and enamine.

[0038] The halides of the above-mentioned nictogen elements and organic ligands can be mixed in a volume ratio of 1:1 to 1:100, specifically 1:10 to 1:50.

[0039] The halogen of the above-mentioned nictogen element and the organic ligand may be mixed at 40 to 100°C, preferably 50 to 70°C, and the reaction time may be 4 to 24 hours, preferably 8 to 16 hours.

[0040] The concentration of the mixture composite produced by the above process may be 0.05 to 1.0 M, preferably 0.1 to 0.5 M, for example 0.2 to 0.3 M.

[0041] Next, a reducing agent can be added to the mixture to combine the nictogen material with an organic ligand. When the reducing agent is added, polyanions of the nictogen element are formed, and these polyanions react with an organic ligand having a double bond to form a copolymer. When synthesizing the polyanionic copolymer, it is possible to additionally add and react the organic ligand after adding the reducing agent, or an excess amount of organic ligand mixed with the nictogen material can react with the polyanions formed after adding the reducing agent to form a copolymer.

[0042] In the present invention, the reducing agent may include one or more of lithium triethylborohydride (superhydride), diisobutylaluminium hydride (DIBAL-H), lithium aluminum hydride (LiAlH4), lithium borohydride (LiBH4), sodium borohydride (NaBH4), aluminum aluminum complex (alane N,N-dimethylethylamine complex, DMEA-AlH3), and tris(dimethylamino)phosphine, and preferably may include a hydride-based reducing agent.

[0043] In the present invention, the concentration of the reducing agent may be 0.5 to 5 M, specifically 1 to 3 M, and the mixture complex and the reducing agent may be mixed in a volume ratio of 1:0.1 to 1:10, specifically 1:0.2 to 1:2.

[0044] The reaction between the above mixture and the reducing agent can be carried out at 40 to 100°C, preferably 50 to 70°C, and the reaction time can be 10 minutes to 4 hours, preferably 20 to 120 minutes, more preferably 30 to 90 minutes.

[0045] In a preferred embodiment of the present invention, an organic solvent may be further added to the mixture, and then a reducing agent may be added to carry out the reaction. The organic solvent may be one or more of the following: a phosphine-based solvent such as trioctylphosphine (TOP) or tributylphosphine; a hydrocarbon-based solvent such as 1-octadecene or 1-undecene; or an amine-based solvent such as octylamine, oleylamine, hexadecylamine, or trioctylamine. In this case, the volume ratio of the mixture complex and the additional organic solvent may be 1:0.5 to 1:10, preferably 1:1 to 1:8.

[0046] Preferably, the organic solvent may include a phosphine-based solvent or a hydrocarbon-based solvent. In this case, since solidification does not occur at room temperature during the preparation of the precursor, it can be stably used for the production of nanocrystals. In this regard, in the embodiments of the present invention, it was confirmed that when an amine-based solvent is used, a problem of solidification at room temperature occurs during the preparation of the precursor, whereas when trioctylphosphine, 1-octadecene, or tributylphosphine solvents are used, solidification does not occur.

[0047] The nictogen polyanionic copolymer precursor prepared according to the present invention comprises a polyanionic structure in which a plurality of nictogen anions are intertwined and a copolymer structure formed by organic ligands. The nictogen polyanionic copolymer precursor of the present invention can be used as a Group V precursor when synthesizing nanocrystals containing a nictogen element (Group V element), such as Group II-V nanocrystals or Group III-V nanocrystals. Since the nictogen polyanionic copolymer precursor according to the present invention has stable reactivity and is easy to handle, it can be usefully used as a Group V precursor.

[0049] In the present invention, the nictogen-based semiconductor nanocrystal may be a nanocrystal formed by combining a group II element and a group V element (nictogen) (II-V nanocrystal) or a nanocrystal formed by combining a group III element and a group V element (nictogen) (III-V nanocrystal).

[0050] In the present invention, the nictogen-based semiconductor nanocrystal is prepared by mixing a group II or group III precursor and a nictogen polyanionic copolymer precursor as a group V precursor.

[0051] In this case, as a Group II or Group III precursor, a halide of a Group II or Group III element can be used.

[0052] Specifically, the group II element may be zinc (Zn), and the halide of the group II element may include zinc chloride, bromide, iodide, fluoride, or a combination thereof. For example, the zinc halide may include one or more of zinc chloride (ZnCl2), zinc bromide (ZnBr2), zinc iodide (ZnI2), and zinc fluoride (ZnF2).

[0053] The above Group III elements may be one or more of indium (In), gallium (Ga), and aluminum (Al), and the halides of the Group III elements may include chlorides, bromides, iodides, fluorides, or combinations thereof of the above Group III elements.

[0054] The above II-V group nanocrystals may be Zn3As2, Zn3P2, or Zn3Sb2 nanocrystals. Additionally, the above III-V group nanocrystals may be InAs, InSb, InP, InAs x Sb 1-x , In y Ga 1-y As, In y Ga 1-y Sb or In y Ga 1-y As x Sb 1-xIt can be (where x and y are each independently greater than 0 and less than 1), preferably InAs.

[0055] The synthesis step of the nanocrystals above can be performed by mixing the Group II or Group III precursor and the nictogen polyanionic copolymer precursor and reacting them at a high temperature. At this time, the nictogen polyanionic copolymer precursor can be used after removing residues through a purification process. In addition, the initial temperature during mixing may be 5 to 50°C, preferably 20 to 30°C, for example, room temperature.

[0056] In the present invention, the molar ratio of the nictogen polyanionic copolymer precursor of the present invention to the group II / III precursor may be 0.1 to 3.

[0057] The reaction between the above precursors can be carried out by a solution process using a heating-up method, a continuous injection method, a hot injection method, etc. The reaction can be carried out at a temperature of 150°C or higher, for example, 200 to 400°C.

[0058] In one embodiment of the present invention, the synthesis of the nanocrystals can be performed using a temperature-raising method. The temperature-raising method is a method of growing crystals while increasing the temperature at a constant rate after mixing precursors. A nictogen polyanionic copolymer precursor is added to a Group II / III precursor at room temperature, and the reaction can be carried out by increasing the temperature at a rate of 0.5 to 10°C / min, preferably 1 to 5°C / min, specifically 2 to 4°C / min. After reaching a synthesis temperature of 200 to 340°C, the nanocrystals can be produced by growing them for 5 minutes to 12 hours, preferably 10 to 30 minutes.

[0059] In one embodiment of the present invention, the synthesis of the nanocrystals may be performed using a continuous injection method. The continuous injection method is used for manufacturing core-shell type nanocrystals, wherein a core is added to a Group II / III precursor, heated to 200 to 340°C, and nanocrystals can be produced by growing them at 200 to 340°C for 5 minutes to 12 hours, preferably 10 to 30 minutes, while continuously injecting a nictogen polyanionic copolymer precursor. During the continuous injection, the injection rate may be 0.1 to 10 mL / h, preferably 0.5 to 5 mL / h, and more preferably 1 to 3 mL / h.

[0060] In one embodiment of the present invention, the synthesis of the nanocrystals may be performed using a hot injection method. The hot injection method may be performed by heating a Group II / III precursor to a synthesis temperature of 200 to 340°C, rapidly injecting a nictogen polyanionic copolymer precursor within a few seconds, e.g. 10 seconds, preferably 5 seconds, and then growing. The growth of the crystals may be performed at 200 to 340°C for 5 minutes to 12 hours, preferably 10 to 120 minutes, more preferably 30 to 90 minutes.

[0061] The novel nictogen polyanionic copolymer precursor of the present invention can be applied to various solution process methods for manufacturing nanocrystals as described above, and can react stably during the manufacturing of nanocrystals. When using the novel nictogen polyanionic copolymer precursor of the present invention, the uniformity, size, stability, and yield of the nanocrystals are superior compared to cases where nanocrystals are manufactured using general Group II / III precursors and Group V precursors, organic ligands, and reducing agents.

[0062] In one embodiment of the present invention, after the reaction is completed, nanocrystals may be obtained by further performing the steps of cooling as needed; purifying; washing; and / or centrifuging. Additionally, it is possible to use the obtained nanocrystals by ligand substitution.

[0063] The crystals obtained according to the present invention may be nanocrystals having an average size (particle diameter) of 5 to 50 nm, preferably 5.5 to 20 nm, and more preferably 6 to 15 nm. In addition, nanocrystals having a particle diameter of 5 nm may be produced in which 50% or more, preferably 70% or more, and more preferably 75% or more of the total is 5 nm. Accordingly, the present invention can be preferably used for the synthesis of nictogen-based quantum dots with a particle diameter of 5 nm or more capable of responding in the SWIR region.

[0065] Accordingly, the present invention may also provide a device comprising the above-mentioned nictogen-based semiconductor nanocrystal, preferably an optoelectronic device. The device may be a diode or a transistor.

[0066] The nictogen-based semiconductor nanocrystals of the present invention have an average particle size of 5 nm or more, and when an optoelectronic device is fabricated using them, light sensitivity in the short wavelength infrared (SWIR) region (generally 900 to 2,500 nm) is possible.

[0067] Specifically, the device of the present invention may include the nictogen-based semiconductor nanocrystalline layer as an active layer.

[0068] The above nanocrystalline layer serves as an active layer of the device and can be formed by coating the nictogen-based semiconductor nanocrystal of the present invention via a solution process. The coating can be performed using spin coating, drop coating, self-assembly coating, layer-by-layer coating, etc.

[0069] One or more solvents such as dimethylformamide, octane, 1,2-ethanedithiol (EDT), sodium sulfide, sodium azide, 1-octanethiol, thiourea, and diethyl zinc may be used as the solvent for the above nanocrystalline coating solution. The concentration of the above nanocrystalline coating solution may be, for example, 1 to 100 mg / mL, but is not limited thereto.

[0070] After coating with the above nanocrystalline coating solution, the solvent is dried to form a nanocrystalline layer. For example, a nanocrystalline layer can be formed by heat treatment at a temperature of 100 to 400°C for 10 to 60 minutes.

[0071] In the present invention, the thickness of the nanocrystalline layer may vary depending on the type of device and the desired performance, and may be, for example, 5 nm to 100 µm, preferably 10 nm to 10 µm, specifically within the range of 100 nm to 1 µm.

[0072] In the present invention, the device may further include components necessary for the device, such as a substrate, one or more electrodes, an electron transport layer, a hole transport layer, and a hole injection layer.

[0073] In the present invention, the electrode may be formed of a metal, a conductive oxide, or a conductive polymer, and may use, for example, metals such as Au, Ag, Pt, and Cu, or conductive oxides such as ITO (indium tin oxide), FTO (fluorine-doped tin oxide), IZO (indium zinc oxide), AZO (aluminum-doped zinc oxide), and GZO (gallium zinc oxide), but is not limited thereto.

[0074] As the electron transport material forming the electron transport layer described above, known metal oxides, etc. may be used. Such metal oxides may consist of materials in which fluorine is doped or bonded to metals such as Al, Cd, Cs, Cu, Ga, Ge, In, and Li, or titanium dioxide (TiO2), zinc oxide (ZnO), zirconium oxide (ZrO), tin oxide (SnO2), tungsten oxide (WO3), tantalum oxide (Ta2O3), etc., which are doped or undoped with Al, Mg, In, Li, Ga, Cd, Cs, Cu, etc., but are not limited thereto.

[0075] The hole transport material forming the hole transport layer described above may include, but is not limited to, metal oxides such as MoO3, TFB (poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(p-butylphenyl))diphenylamine)]), CBP (4,4'-N,N'-dicarbazolyl-biphenyl), polyaniline, polypyrrole, etc.

[0076] One or more hole injection materials forming the hole injection layer above may be used, such as PEDOT:PSS (poly(ethylenedioxy)thiophene):polystyrene sulfonate), PEDOT (poly(ethylenedioxy)thiophene), polyaniline, polypyrrole, polythiophene, polyacetylene, polyphenylene, etc., but are not limited thereto.

[0077] The nanocrystalline layer used as an active layer in the device of the present invention includes the nictogen-based semiconductor nanocrystal of the present invention and can exhibit characteristics capable of photosensitive in the Short Wavelength InfraRed (SWIR) region (generally 900 to 2,500 nm). Therefore, the nanocrystal of the present invention can be usefully used in a device that responds in the infrared region.

[0079] Examples

[0081] The present invention will be explained in more detail through the following examples. However, these examples represent some experimental methods and compositions to illustrate the invention, and the scope of the invention is not limited to these examples.

[0083] Preparation Example 1: Preparation of a Pictogen Polyanionic Copolymer Precursor

[0085] 1-1. Preparation of Pictogen Polyanionic Copolymer Precursors Using Pictogen Materials and Organic Ligands

[0087] A polyanionic copolymer precursor was synthesized using a nictogen precursor and an organic ligand according to the reaction mechanism of Fig. 1 and the process shown in Fig. 2.

[0088] 0.42 mL of 3 AsCl, a nictogen precursor, was mixed with 20 mL of degassed oleylamine and stirred on a hot plate at 60°C for 12 hours to prepare an As complex with a concentration of 0.25 M. Then, 2.75 mL of degassed oleylamine and 1.25 mL of a 2 M superhydride (SH, Lithium triethylborohydride) reducing agent were added to 1 mL of the As complex, and the mixture was stirred on a hot plate at 60°C for 1 hour to prepare a novel nictogen polyanionic copolymer precursor. A photograph of the prepared nictogen polyanionic copolymer precursor (at room temperature) is shown in Figure 3.

[0090] 1-2. Preparation of Pictogen Polyanionic Copolymer Precursors Using Pictogen Materials, Organic Ligands, and Solvents

[0092] A polyanionic copolymer precursor was synthesized using a nictogen precursor and an organic ligand according to the process shown in Fig. 4.

[0093] 0.42 mL of 3 AsCl, a nictogen precursor, was mixed with 20 mL of degassed oleylamine and stirred on a hot plate at 60°C for 12 hours to prepare an As complex with a concentration of 0.25 M. Then, 2.75 mL of trioctylphosphine was added to 1 mL of the As complex and 1.25 mL of a superhydride (SH) reducing agent with a concentration of 2 M was mixed, and the mixture was stirred on a hot plate at 60°C for 1 hour to prepare a novel nictogen precursor. A photograph of the prepared nictogen polyanionic copolymer precursor (at room temperature) is shown in Fig. 5.

[0095] Comparative Example 1: Preparation of an As precursor complex using a nictogen and an organic ligand

[0097] AsCl3, a nictogen precursor, was combined with degassed oleylamine and stirred on a hot plate at 60°C for 12 hours to prepare an As complex with a concentration of 0.25 M. Subsequently, the prepared complex was cooled to room temperature. A photograph of the prepared complex is shown in Fig. 6.

[0099] Preparation Example 2: Synthesis of Pictogen-Based Nanocrystals

[0101] 2-1. Synthesis of Pictogen-Based Nanocrystals Using the Heating Method

[0103] Pictogen-based semiconductor compound nanocrystals were synthesized by a heating method using the nictogen polyanionic copolymer precursor and Group III precursor of Preparation Example 1.

[0104] In the case of the heating method, 5 mL of the above-mentioned nictogen polyanionic copolymer precursor was added to 10 mL of a Group III precursor (InCl3) in a nitrogen atmosphere at room temperature, and nanocrystals were obtained by heating at a rate of 3 °C / min and growing at a synthesis temperature of 300 °C for 15 minutes.

[0106] 2-2. Synthesis of Nictogen-Based Nanocrystals Using Continuous Injection Method

[0108] Pictogen-based semiconductor compound nanocrystals were synthesized by a continuous injection method using the nictogen polyanionic copolymer precursor and Group III precursor of Preparation Example 1.

[0109] For the continuous injection method, 40 mg of InAs core was added to 20 mL of Group III precursor in a nitrogen atmosphere and heated to 250°C. Then, 10 mL of nictogen polyanionic copolymer precursor was continuously injected at a rate of 2 mL / h, and nanocrystals were obtained by growing at 250°C for 15 minutes.

[0111] 2-3. Synthesis of Piktogen-based Nanocrystals Using High-Temperature Implantation Method

[0113] Pictogen-based semiconductor compound nanocrystals were synthesized by a high-temperature implantation method using the nictogen polyanionic copolymer precursor and Group III precursor of Preparation Example 1.

[0114] In the case of the high-temperature injection method, 10 mL of a Group III precursor was added in a nitrogen atmosphere and heated to a synthesis temperature of 250°C. Then, 5 mL of a nictogen polyanionic copolymer precursor was rapidly injected within seconds, and nanocrystals were obtained by growing for 1 hour.

[0116] Comparative Example 2: Synthesis of nictogen-based nanocrystals using conventional As precursors

[0118] Pictogen-based semiconductor compound nanocrystals were synthesized by the heating method using the As complex precursor and Group III precursor of Comparative Example 1.

[0119] 1 mL of the As complex of Comparative Example 1 was added to 10 mL of a Group III precursor at room temperature, heated to the reaction temperature at a constant rate of 3 °C / min, and grown at a synthesis temperature of 300 °C for 15 minutes to obtain nanocrystals.

[0121] Preparation Example 3: Fabrication of an infrared optoelectronic device using pectogen-based nanocrystals

[0123] Pyctogen-based InAs nanocrystals were fabricated using the method of Preparation Example 2-1, and an infrared optoelectronic device with a reverse structure was fabricated using them. The structure of the optoelectronic device utilized an electron transport layer (ZnO) / active layer (InAs) / hole transport layer (MoO3), and a diode-type infrared device that responds in the infrared region was fabricated.

[0125] Comparative Example 3: Fabrication of an infrared optoelectronic device using pectogen-based nanocrystals

[0127] Piktogen-based InAs nanocrystals were fabricated using the method of Comparative Example 2, and an infrared optoelectronic device with a reverse structure was fabricated using them. The structure of the optoelectronic device utilized an electron transport layer (ZnO) / active layer (InAs) / hole transport layer (MoO3), and a diode-type infrared device that responds in the infrared region was fabricated.

[0129] Experimental Example 1: Mass Spectrometry Experiment of Pyctogen Polyanionic Copolymer Precursor

[0131] MALDI-TOF mass spectrometry was performed on the piktogen polyanionic copolymer precursor of Preparation Example 1-1 and the precursor after purification. In addition, nuclear magnetic resonance (NMR) analysis was performed on the piktogen polyanionic copolymer precursor of Preparation Example 1-1 and the organic ligand.

[0132] Figures 7a and 7b show the MALDI-TOF mass spectrometry results of the nictogen polyanionic copolymer precursor (a) and the precursor after purification (b), respectively, and Figure 8 shows the NMR analysis results.

[0133] MALDI-TOF mass spectrometry results showed peaks corresponding to the molecular weights of As3-OLAM, As4-OLAM, or polymers with additional ion bonds, which are polymerized forms of As anion and oleylamine. NMR analysis confirmed that peaks c and d, corresponding to the double bond peak of oleylamine, were reduced in the nictogen polyanionic copolymer precursor compared to the organic ligand. From these results, it was found that the nictogen polyanionic copolymer was prepared according to the proposed reaction mechanism.

[0135] Experimental Example 2: Mass Spectrometry Experiment of Modified Pyctogen Polyanionic Copolymer Precursor

[0137] MALDI-TOF mass spectrometry was performed on the nictogen polyanionic copolymer precursor (SH w / TOP) of Preparation Example 1-2. The same experiment was performed on a precursor (SH w / ODE) prepared using the method of Preparation Example 1-2 but with 1-octadecene (ODE) instead of TOP, and on a precursor (0.4 SH w / TOP and 0.4 SH w / ODE) prepared using TOP or ODE and 0.4 mL of 2 M SH reducing agent. Photographs of each sample (from left: 0.4 SH w / TOP, 0.4 SH w / ODE, SH w / TOP, and SH w / ODE) and the corresponding MALDI-TOF mass spectrometry results are shown in Figures 9 and 10, respectively.

[0138] As a result of MALDI-TOF mass spectrometry, peaks corresponding to the molecular weights of As3-OLAM, As4-OLAM, As5-OLAM, As7-OLAM, As3-(OLAM)2, which are polymerized forms of As anion and oleylamine, or additionally ion-bonded polymers appeared. Accordingly, it can be seen that when the modified nictogen polyanionic copolymer precursor was prepared, a copolymer of polyanions and organic ligands was also formed.

[0140] Experimental Example 3: Analysis of Absorption Spectra and TEM Images According to Nanocrystal Preparation Method and Type

[0142] For each InAs nanocrystal prepared using the methods of Preparation Examples 2-1, 2-2, and 2-3 and the InSb nanocrystal prepared using the method of Preparation Example 2-3, the absorption spectrum and transmission electron microscope (TEM) image of each nanocrystal were analyzed.

[0143] FIGS. 11 to 13 show experimental results for InAs nanocrystals prepared by different preparation methods according to Preparation Examples 2-1 to 2-3, respectively, and FIG. 14 shows experimental results for InSb nanocrystals prepared using the high-temperature injection method of Preparation Example 2-3 but using Sb as the nictogen element.

[0144] According to the experimental results, when using the heating method, nanocrystals of uniform size were formed with peaks appearing in the absorption spectrum, and it was confirmed that the synthesis of shell-shaped InAs (InAs shell) was possible when using the continuous injection method. Meanwhile, when InAs and InSb were prepared using the same methods, it was confirmed that the uniformity of the InAs nanocrystals was superior.

[0146] Experimental Example 4: Analysis of Nanocrystal Characteristics According to Precursor Type

[0148] Absorption spectra, transmission electron microscope (TEM) images, and crystal particle size distributions were analyzed for InAs nanocrystals prepared by the method of Preparation Example 2-1 using the precursor of Preparation Example 1-2 and InAs nanocrystals prepared by the method of Comparative Example 2.

[0149] Figures 15a and 15b show the absorption spectra of the InAs nanocrystal of the prepared example (a) and the nanocrystal of the comparative example (b), respectively; Figures 16a and 16b show the TEM images of the InAs nanocrystal of the prepared example (a) and the nanocrystal of the comparative example (b), respectively; and Figures 17a and 17b show the particle size distribution of the InAs nanocrystal of the prepared example (a) and the nanocrystal of the comparative example (b), respectively.

[0150] Experimental results showed that when the nictogen polyanionic copolymer of the present invention was used as a Group V precursor during the preparation of nanocrystals, the crystal uniformity was high and the nanocrystal size was larger. Accordingly, it was found that using the precursor of the present invention is advantageous for the synthesis of nanocrystals with a particle size of 5 nm or larger, and that the uniformity is also excellent.

[0152] Experimental Example 5: Analysis of Physical Properties of Precursors According to Solvent Type

[0154] A nictogen polyanionic copolymer precursor was prepared using the method of Preparation Example 1-2, but using oleylamine, 1-octadecene, octylamine, oleic acid, or tributylphosphine instead of TOP as the solvent, and a photograph of the prepared precursor is shown in FIG. 18.

[0155] Experimental results confirmed that when trioctylphosphine, 1-octadecene, and tributylphosphine were used as solvents, coagulation did not occur at room temperature, whereas when oleylamine, oleic acid, and octylamine were used, coagulation occurred at room temperature. Accordingly, it was confirmed that phosphine-based or hydrocarbon-based solvents are preferred as solvents.

[0156] Based on the results confirmed in the above experiment, InAs nanocrystals were prepared using the method of Preparation Example 2 using a solvent (trioctylphosphine, 1-octadecene and tributylphosphine) that does not cause solidification.

[0157] Figures 19a, 19b, and 19c show the absorption spectra of nanocrystals prepared using precursors with trioctylphosphine (a), 1-octadecene (b), and tributylphosphine (c), respectively, and it was found that the particle size was the largest and the uniformity was excellent when trioctylphosphine was used.

[0159] Experimental Example 6: Yield Analysis According to Nanocrystal Manufacturing Process

[0161] InAs nanocrystals were prepared using the precursor of Preparation Example 1-2 by the method of Preparation Example 2-1. At this time, 0.5 mmol, 0.25 mmol, 2.5 mmol, 2.75 mL, and 11 mL of InCl3, AsCl3, SH reducing agent, TOP, and oleylamine were used, respectively, for the preparation of the precursor and nanocrystals.

[0162] For comparison, nanocrystals were prepared using a conventional As precursor, an organic ligand, and SH. Specifically, InAs nanocrystals were prepared by mixing 30.5 mmol of InCl and 30.25 mmol of AsCl with 11 mL of the organic ligand oleylamine and reducing it by adding 2.5 mmol of SH. The heating method was used for all of the nanocrystal preparations, and the mixture was heated to 300℃ at a rate of 3℃ / min.

[0163] FIGS. 20a and 20b show the absorption spectra of nanocrystals (a) prepared by the method of the preparation example and nanocrystals (b) prepared using a conventional As precursor, respectively. It can be seen that when a copolymer precursor is prepared and nanocrystals are prepared according to the present invention, the uniformity of the particles is superior and the size is larger compared to when each precursor is co-reduced.

[0164] In addition, as described above, a total of 42.5 mg of nanocrystals were obtained using the preparation example under conditions where the amounts of the halide, oleylamine, and SH reducing agent were the same, whereas the yield was 26.2 mg when using the conventional method, confirming a result with a lower yield. Thus, it was found that the yield of nanocrystals is also excellent when using the copolymer precursor of the present invention.

[0166] Experimental Example 7: IV Analysis of Optoelectronic Devices

[0168] An optoelectronic device was fabricated using the method of Preparation Example 3, utilizing InAs nanocrystals synthesized by the continuous injection method according to the method of Preparation Example 2-2. IV analysis was performed on the fabricated device in the 970 nm and 1,050 nm regions, and the results are shown in Fig. 21.

[0169] Referring to the experimental results, when a reverse voltage of -1V is applied, the dark current in the 970nm and 1,050nm regions is approximately 10- -6 A, photocurrent is about 10 -4 It was confirmed that the current increased by about 100 times when infrared wavelength light was irradiated with A.

[0170] Accordingly, it was confirmed that the photoelectric performance of the nanocrystals manufactured using the present invention is excellent.

[0172] Experimental Example 8: IV Analysis of Optoelectronic Devices According to Precursor Type

[0174] InAs nanocrystals were fabricated using the copolymer precursor of Preparation Example 1-2 and the precursor of Comparative Example 1, respectively, by the continuous injection method of Preparation Example 2-2. Optoelectronic devices were fabricated using the fabricated InAs nanocrystals by the method of Preparation Example 3. IV measurements were performed on each optoelectronic device in the 1,100 nm region, and the IV graphs of the Comparative Example (left) and Preparation Example (right) are shown in FIG. 22.

[0175] According to the experimental results, it was confirmed that when using the copolymer precursor according to the present invention, the degree of light sensitivity is greater and the dark current value is lower when a reverse voltage is applied compared to when using the precursor of Comparative Example 1 (conventional As precursor). Accordingly, it was found that when an optoelectronic device is fabricated using InAs nanocrystals produced through the nictogen polyanion copolymer precursor, the dark current characteristics and photosensitivity are excellent.

[0177] Although some embodiments of the present invention have been described above, the present invention is not limited to the embodiments described above but may be implemented with modifications and variations within the scope of the gist of the invention, and such modified and varied forms should also be understood as belonging to the technical spirit of the present invention.

Claims

Claim 1 A method for preparing a nictogen polyanionic copolymer precursor, comprising the steps of: mixing a halide of a nictogen (Group V) element and an organic ligand containing one or more double bonds within the molecule; and adding a reducing agent to the mixture and further reacting it with the organic ligand to prepare a nictogen polyanionic copolymer. Claim 2 A method for preparing a nictogen polyanionic copolymer precursor according to claim 1, wherein the halogen of the nictogen element is one or more selected from the group consisting of arsenic trichloride (AsCl3), arsenic tribromide (AsBr3), arsenic triiodide (AsI3), antimony trichloride (SbCl3), antimony tribromide (SbBr3), antimony triiodide (SbI3), phosphorus trichloride (PCl3), phosphorus tribromide (PBr3), and phosphorus triiodide (PI3). Claim 3 A method for preparing a nictogen polyanionic copolymer precursor according to claim 1, wherein the organic ligand comprises one or more selected from the group consisting of oleylamine, oleic acid, palmitoleic acid, linoleic acid, linoleylamine, and enamine. Claim 4 A method for preparing a nictogen polyanionic copolymer precursor according to claim 1, wherein the mixture is prepared by reacting the halide of the nictogen element and an organic ligand at 40 to 100°C for 4 to 24 hours. Claim 5 A method for preparing a nictogen polyanionic copolymer precursor according to claim 1, wherein the reducing agent comprises one or more selected from the group consisting of lithium triethylborohydride (superhydride), diisobutylaluminium hydride (DIBAL-H), lithium aluminum hydride (LiAlH4), lithium borohydride (LiBH4), sodium borohydride (NaBH4), alane N,N-dimethylethylamine complex (DMEA-AlH3), and tris(dimethylamino)phosphine. Claim 6 A method for preparing a nictogen polyanionic copolymer precursor, wherein, in the step of adding a reducing agent, the organic ligand is additionally added. Claim 7 A method for preparing a nictogen polyanionic copolymer precursor according to claim 1, further comprising the step of adding an organic solvent before adding a reducing agent to the complex. Claim 8 A method for preparing a nictogen polyanionic copolymer precursor according to claim 7, wherein the organic solvent comprises one or more selected from the group consisting of trioctylphosphine (TOP), tributylphosphine, 1-octadecene, 1-undecene, octylamine, oleylamine, hexadecylamine, and trioctylamine. Claim 9 A method for manufacturing a nictogen-based semiconductor nanocrystal, comprising: a nictogen polyanionic copolymer precursor prepared by the method of any one of claims 1 to 8; and a step of reacting a Group II or Group III precursor to produce a nanocrystal. Claim 10 A method for manufacturing a nictogen-based semiconductor nanocrystal according to claim 9, wherein the nanocrystal manufacturing step comprises: a step of preparing a mixture by adding a nictogen polyanionic copolymer precursor to a Group II or Group III precursor; a step of increasing the temperature of the mixture at a rate of 0.5 to 10℃ / min to reach a synthesis temperature of 200 to 340℃; and a step of growing crystals at the synthesis temperature for 5 minutes to 12 hours. Claim 11 A method for manufacturing a nictogen-based semiconductor nanocrystal according to claim 9, wherein the nanocrystal manufacturing step comprises: a step of adding a core material to a Group II or Group III precursor and then heating to 200 to 340°C; and a step of growing a crystal at 200 to 340°C for 5 minutes to 12 hours while continuously injecting a nictogen polyanionic copolymer precursor into the heated precursor. Claim 12 A method for manufacturing a nictogen-based semiconductor nanocrystal according to claim 9, wherein the nanocrystal manufacturing step comprises: heating a Group II or Group III precursor to 200 to 340°C; injecting a nictogen polyanionic copolymer precursor into the heated precursor within 10 seconds; and growing a crystal at 200 to 340°C for 5 minutes to 12 hours after the precursor injection. Claim 13 A method for manufacturing a nictogen-based semiconductor nanocrystal according to claim 9, wherein the average particle size of the manufactured nanocrystal is 5 to 50 nm. Claim 14 An optoelectronic device comprising an active layer formed using a nictogen-based semiconductor nanocrystal manufactured by the method of claim 9. Claim 15 In claim 14, the optoelectronic device is sensitive to light in the Short Wavelength InfraRed (SWIR) region.

Citation Information

Patent Citations

  • Quantum dot, production method thereof, and electronic device including the same

    KR1020190085884A

  • Method for Preparing III-V Quantum Dot Using Coordinated Complex of Halogenated Metal, III-V Quantum Dot Prepared Thereby and Device Using Same

    KR1020220143598A

  • Quantum dots and production method thereof

    KR1020190141622A

  • Quantum dot and preparing method of the same

    KR1020220073641A